Evaluación del desperdicio de alimentos: normas y acciones para fomentar la circularidad en Perú - Huiman Cruz, Alberto (2024)
Population growth generates a greater demand for food, thus increasing food waste. The fight against this problem began in several countries with strict regulations managing food waste. In the case of Peru, an analysis of progress in the field is presented. The objective of the article is to analyze the management of food waste in Peru and worldwide, both in terms of regulations and current situation; for this purpose, a bibliographic review was conducted taking into account the guidelines of circularity in food. The results obtained demonstrate deficiencies in both Peruvian and global regulatory frameworks, with the exception of Europe. The increase in food waste generation was analyzed globally in households, retail establishments, and the service industry. Countries share concerns about the increase in waste and seek to align themselves with the circularity model. In the case of Peru, this implies modifying and improving regulations with the involvement of relevant stakeholders. Therefore, actions are proposed to promote circularity in food management with a sustainability vision, such as proposals for national actions and basic principles, with collaboration between industries, government, and civil society.